Desain Turbin Pelton Kapasitas 26 kW pada Pembangkit Listrik Tenaga Mikrohidro (Studi Kasus: Kampung Nehibe): A Design of Pelton Turbine with Capacity of 26 kW for Micro-Hydro Power Plant (Case Study: Nehibe Village) - Evenly Evenly; Pither Palamba; Marthen Liga; Johni Jonatan Numberi; Endang Hartiningsih; Thobby Wakarmamu; Tiper K. M. Uniplaita (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
The need for electrical energy in Nehibe village is currently increasing along with the increase in population and new households. The demand for electricity in this village reaches 18 kW, with an average power per household of 450 VA. The problem is that Hachakwa Nehibe Micro Hydro Power Plant (PLTMH), which is very close to the village, has a capacity of only 10 kW. Based on that problem, this study aims to design a peltor turbine with two nozzles for the new 26 kW PLTMH. This power plant uses the water from the Tena Mroway and Yora Mroway rivers, which are located 2 km from the end of the village, as a new source of energy. This design of the turbine is based on the mathematical equations, measurement data of the head, and the flow of the rivers. This research shows that the Pelton turbine with two nozzles (nj), 0.032 meters of jet diameter (Dj), 0.330 meters of runner diameter (Dr), 0.096 meters of bucket diameter, and 21 buckets can produce 26 kW of power with 60 ltr/sec of river flow and 77 meters of head height. This specialization can be used to develop the new PLTMH in Nahibe Village.